Development and Validation of the Relativity Concept Inventory Test Using Item Response Theory Generalized Partial Credit Model 3PL - Mafudi, Innal; Istiyono, Edi (FKIP Universitas Lampung, 2024)
Abstract: This research aims to develop a valid and reliable Relativity Concept Inventory Test instrument. This instrument is based on relativity material, which includes Einstein's first and second postulates, time dilation, velocity addition, and length contraction. Methods for preparing instruments include 1) test design, 2) test validation, 3) test trials, and 4) test data analysis. The design of the test grid is based on Bloom's taxonomy C2 to C5 and produces 13 questions. The instrument is made in the form of multiple-choice questions and is equipped with a level of confidence. Instrument validation was carried out by 6 physics education lecturers and 1 high school teacher, with analysis using the V Aiken formula. The validated instrument was then tested on 130 students from 2 high schools in Madiun. Trial data was analyzed using the Generalized Partial Credit Model 3PL (GPCM-3PL). The development results show that: 1) 13 multiple choice Relativity Concept Inventory Test questions with a level of confidence were successfully developed, 2) expert validation showed that all question items got a score of 0.93, which is included in the valid, with instrument reliability of 0, 42 (very low category), 3) the results of the trial test showed that the relativity concept inventory was proven to be fit with the GPCM, with different power of the items of 0.407 and the level of difficulty showed that 11 items were valid with a range of -1.05 to 1.64, while 2 questions (numbers 8 and 9) are invalid with a value of more than -2. Apart from that, the question items have no potential to be guessed, as evidenced by the guessing value of 0 (zero). This Relativity Concept Inventory Test instrument meets the requirements for use in measuring students' conceptual understanding Keywords: assessment, inventory concept, relativity. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp142-154